2018
DOI: 10.3855/jidc.9580
|View full text |Cite
|
Sign up to set email alerts
|

First molecular characterisation and PCR ribotyping of Clostridium difficile strains isolated in two Algerian Hospitals

Abstract: Introduction: Clostridium difficile is the major etiological agent of nosocomial antibiotics associated diarrhoea. C. difficile infection is associated with considerable morbidity and mortality among hospitalized patients worldwide. Despite its known importance, there is no study on this important pathogen in Algeria. Methodology: In this prospective study, undertaken between 2013 and 2015, faecal specimens were collected from 159 hospitalized patients with antibiotic-associated diarrhoea in two tertiary healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
4
10
1
Order By: Relevance
“…However, in the isolates from Ghana (40%, n = 6/15) and Algeria (36.4%, n = 4/11) in Africa, RT 084 was the most prevalent and with an equal distribution between symptomatic patients and asymptomatic controls. In addition, all were found to be nontoxigenic and resistant to erythromycin and ciprofloxacin [45][46][47]. When comparing the age groups, the overall ribotype diversity was higher in patients aged ≥81 years which is consistent with the results from a multicentre study performed in Europe [48].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, in the isolates from Ghana (40%, n = 6/15) and Algeria (36.4%, n = 4/11) in Africa, RT 084 was the most prevalent and with an equal distribution between symptomatic patients and asymptomatic controls. In addition, all were found to be nontoxigenic and resistant to erythromycin and ciprofloxacin [45][46][47]. When comparing the age groups, the overall ribotype diversity was higher in patients aged ≥81 years which is consistent with the results from a multicentre study performed in Europe [48].…”
Section: Discussionsupporting
confidence: 82%
“…Surprisingly, several RTs identified in our study carried toxin genes (RTs 031, 038, 039, 084, 085) but in other studies an absence of the toxin genes in these ribotypes was identified [28,[45][46][47][48][49][50][51]. The differences in PaLoc arrangements in certain RTs were also noted previously.…”
Section: Discussionsupporting
confidence: 74%
“…There was minimal overlap in types between regions, with only ribotype 084 being found in both locations. This strain has also be reported in humans and animals in different countries, including Africa (Djebbar et al, ; Janezic, Ocepek, Zidaric, & Rupnik, ). This non‐toxigenic ribotype was the 2nd most common strain in Nigerian dogs and was the predominant type in two studies of humans in Ghana, another West African country (Janssen et al, ; Seugendo et al, ).…”
Section: Discussionmentioning
confidence: 69%
“…A small study from Ghana revealed only three toxigenic isolates out of a total of fi ft een [99]. Th e most frequent (non-toxigenic) RT was RT084 as seen in the Algerian study [97]. In another study conducted in Tanzania only seven isolates could be retrieved including three RT038, two RT045 and two unknown RTs [100].…”
Section: Epidemiology In Africamentioning
confidence: 99%
“…In Algeria one study has been published so far including only 11 isolates of which four were non-toxigenic (RT084) and the other seven strains included mainly RT014 and RT020 [97]. In South Africa for instance in a small study including 32 isolates RT017 was most prevalent (50%) while 16% of all isolates were RT001 [98].…”
Section: Epidemiology In Africamentioning
confidence: 99%